Stock market development and economic growth: An empirical analysis between Turkey and BRICS countries - (:unkn) unknown (Springer, 2015)
There is an overwhelming consensus that vibrant stock markets exceedingly affect countries’ economic progress. This paper tries to examine the complex linkages between stock market development and economic growth employing market capitalization ratio, turnover ratio and total value of shares traded as percent of GDP as proxies to stock market development while GDP per capita and FDI as a percentage of GDP to gauge economic development of BRICS (Brazil, Russia, India, China and South Africa) and Turkey. Significant positive links were revealed by VAR results, indicating that stock market development positively and significantly affects the economic growth of Russia, India and China. The Ganger causality test model uncovers that stock market development significantly and robustly influences economic growth for Russia, India, Turkey and South Africa whereas for Brazil and China, it is the economic growth which promotes stock market progress through enhancing liquidity. The complexities of stock markets and their relationship with economic growth prevented us from generalizing their positive link. Accordingly, the need of further research is apparent in order to obtain more evidence about their interaction. © Springer International Publishing Switzerland 2015.
Keywords: BRICS countries; Complexity; Economic growth; Stock market development